Reduced electrical performance of Zn enriched ZnTe nanoinclusion semiconductors thin films for buffer layer in solar cells. (1st June 2017) - Mahmood, Waqar; Thomas, Andrew; Haq, Anwar ul; Shah, Nazar Abbas; Nasir, Muhammad Farooq
Abstract: Closed space sublimation (CSS) technique was employed to deposit thin films of zinc telluride (ZnTe) on a glass substrate under high vacuum. Two sets of ZnTe thin films and Zn enriched ZnTe thin films were prepared for comparative study. The enrichment for Zn onto the as-deposited ZnTe thin films was done by the novel manner of layer by layer deposition with subsequent annealing. X-ray diffraction (XRD) studies revealed before and after the enrichment of Zn the preferred orientation is [1 1 1] having cubic phase. The lattice constant was found to be increased and the crystallite size decreased 28 nm to 24 nm after the enrichment of Zn. A morphological study was carried out through a scanning electron microscope (SEM). For Zn enriched samples the average grain size is smaller as compared to ZnTe thin films. The local compositions of Zn and Te were confirmed by energy dispersive x-rays (EDX) from 51 atomic % of as-deposited ZnTe thin films to 68 atomic % in Zn enriched ZnTe thin films. The Zn enriched samples have a slight decrease in optical transmission in UV–VIS–NIR range as compared to the as-deposited ZnTe thin films. Due to the deposition of Zn there is a very small change in optical band gap energy. A four-probe technique was used to study electrical properties of as-deposited and Zn-enriched ZnTe thin films. These results shows that the as-deposited samples had the resistivity of 10 6 Ω · cm. For Zn enrichment samples resistivity increases from 10 6 Ω · cm to 10 8 Ω · cm, which shows that Zn-enriched samples are not suitable for back contact of II–VI solar cells. X-rays photoelectron spectroscopy (XPS) was used to confirm the elemental compositions and its bonding strength before and after the enrichment of Zn.